Dietary counseling is associated with an improved lipid profile in children with familial hypercholesterolemia. (September 2016) - Torvik, Kristin; Narverud, Ingunn; Ottestad, Inger; Svilaas, Arne; Gran, Jon Michael; Retterstøl, Kjetil; Ellingvåg, Asta; Strøm, Ellen; Ose, Leiv; Veierød, Marit B.; Holven, Kirsten B.
Abstract: Background and aims: Familial hypercholesterolemia (FH) is a genetic disorder characterized by elevated levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C). Guidelines recommend cholesterol-lowering medication from 8 to 10 years of age and dietary recommendations. Little is known about the diet of FH children and the effect of dietary counseling. The aim of the study was to describe the diet of FH children with respect to fat quality, and to investigate if dietary counseling improved lipid profile. Methods: Fifty-four FH children (5–18 years) were included in the study and dietary intake was recorded with a pre-coded food diary for four days. Information about plasma lipid levels was obtained. Results: Median intake of total fat, monounsaturated fat, polyunsaturated fat (PUFA) and saturated fat (SFA) was 30.8, 10.4, 5.9 and 12.0 E %, respectively. Among non-statin treated FH children, SFA intake was significantly correlated with TC, LDL-C and apolipoprotein (apo) B (rsp  = 0.55; p  = 0.004, rsp  = 0.46; p  = 0.02, and rsp  = 0.45; p  = 0.02, respectively), and PUFA/SFA ratio significantly inversely correlated with TC (rsp  = −0.42; p  = 0.03). Compared to the first visit, non-statin and non-plant sterol treated FH children (n = 10) had significantly reduced levels of TC ( p  < 0.01), LDL-C ( p  = 0.01), high-density lipoprotein cholesterol ( p  = 0.02), apo B ( p  = 0.05) and apo A-1 ( p  = 0.02) levels at a later visit. Conclusions: FH children had a higher intake of SFA than recommended and the SFA intake was positively correlated with plasma TC, LDL-C and apo B levels in FH children not using statins. Importantly, the plasma lipid profile was improved in FH children after dietary counseling where focus was on reducing intake of SFA and dietary cholesterol. Highlights: Guidelines recommend cholesterol-lowering medication and dietary recommendations from 8 to 10 years of age. Little is known about the diet of children with FH and the effect of dietary counseling on plasma lipid Levels. FH children had a higher intake of SFA than recommended. SFA intake was positively correlated with plasma TC, LDL-C and apoB levels in FH children not using statins. The plasma lipid profile was improved in FH children after dietary counseling where focus was on reducing intake of SFA and dietary cholesterol.